Defect-induced ferromagnetism in a S = 1/2 quasi-one-dimensional Heisenberg antiferromagnetic chain compound - Zhe Wang (Nature Portfolio, 2021)
Abstract We present evidences that defects in the spin S = 1/2 Heisenberg antiferromagnetic chain (HAFC) compound can lead to ferromagnetism by studying the magnetic and thermal properties of the newly discovered quasi-one-dimensional (1D) metal–organic framework [CH3NH3][Cu(HCOO)3] (MACuF). Our findings suggest that the long-range ferromagnetic order at 3.7 K can be attributed to Cu2+ ions from the 2D networks constructed by the endpoints of the broken chains. In such a case, the intrinsic magnetism can emerge in this quasi-1D Heisenberg chain system at the background of the short-range antiferromagnetism. This unusual ferromagnetism found in HAFC not only enriches magnetic features in the low-dimensional systems, but helps to understand some of the exotic magnetic phenomena in other real quasi-1D magnetic materials.